Economic shocks and structural adjustments : Turkey after 1973 - Conway, Patrick J. (Amsterdam ; New York : North-Holland ; New York : Sole distributors for the U.S.A. and Canada, Elsevier Science Pub. Co., 1987)
This book was designed to reveal the economics shocks encountered by Turkey in the year 1973.
Includes bibliographical references: p. 207-219.
asm 23/01/2019
Loans
Keywords: Economic policy---Econometric models; Economic conditions---Econometric models; Turkey